Monetary and Exchange Rate Policies of the Euro Area : The Euro Area Stability Programs. (IMF Staff Country Reports; Country Report, 2000)
This report describes the monetary and exchange rate policies of the euro area and the euro area stability programs. The Stability and Growth Pact presents annual stability programs (SPs), which outlines the medium-term fiscal objectives. The paper provides a preliminary review of the SPs, assesses the previous fiscal developments, and analyzes the medium-term prospects implied by the new SPs. The study describes the revised stability program and also the past and prospective fiscal adjustment in the euro area as a whole and at the disaggregated level.